"I'm not here to push you:" raising adolescents' treatment engagement via autonomy support. (May 2023) - van Dijk, Anouk; Brummelman, Eddie; de Castro, Bram Orobio
Abstract: More than 45% of adolescents with aggressive behavior problems drop out of treatment prematurely. Building on insights from self-determination theory, we examined in three studies whether clinicians can raise adolescents' treatment engagement by supporting their autonomy. In an interview study (Study 1), clinicians ( N = 16; 43.8% female; ages 30–57) spontaneously described 12 times more autonomy-supportive than controlling strategies to engage adolescents. In a preregistered experiment (Study 2), clinicians ( N = 68; 88.2% female; ages 23–65) were confronted with videos of adolescents displaying resistance. We manipulated the DSM diagnosis of adolescents to indicate either aggressive behavior problems or other problems. We found that, regardless of diagnosis, clinicians used both autonomy-supportive strategies (57.7% of responses) and controlling strategies (39.3%), suggesting that applying autonomy support can be challenging with any adolescent displaying resistance. In an experimental study (Study 3), adolescents ( N = 252; 50.0% female; ages 12–17) reported higher therapeutic alliance ( d = 0.95, 95% CI [0.80, 1.10]) and treatment engagement ( d = 0.77, 95% CI [0.63, 0.91]) after listening to audio-recorded autonomy-supportive versus controlling responses from clinicians, regardless of whether these adolescents had aggressive behavior problems. Overall, this research suggests that clinicians can raise adolescents' treatment engagement through autonomy support. Highlights: We examined how clinicians may raise adolescent treatment engagement. In interviews (Study 1), clinicians emphasized the importance of autonomy support. In observations (Study 2), clinicians used both autonomy support and control. In an experiment (Study 3), clinician autonomy support raised adolescent engagement. Autonomy support can be a critical strategy to reduce adolescent treatment dropout.